Centro de Estudios e Investigaciones Regionales y Agrarias: Investigaciones y propuestas geográficas - Alves Lacerda, Édipo (2025)
The book, organized by Gustavo Henrique Cepolini Ferreira, Anderson Willians Bertholi, Deyvison Lopes de Siqueira and Gislene Quaresma Oliva, brings together texts by researchers from the State University of Montes Claros (Unimontes) who are committed to critical and engaged geography. The chapters are the result of research and extension activities focused on popular struggles in defense of land, traditional territories and peasant life. The book covers topics such as agrarian reform, peasantry, agroecology, environmental impacts, urban agriculture, structural racism, land regularization, social movements, geographic education and other aspects of rural development in the Semi-Arid and other regions of northern Minas Gerais. Divided into thirteen chapters, the book discusses the conflicts generated by the advance of agribusiness, disputes over territory and natural resources, the effects of climate change on peasant-family farming, the importance of community-based tourism and the challenges faced by quilombolas, indigenous and traditional communities in the context of Minas Gerais and Brazil.